Rootstock induced epigenetic variation in Hevea brasiliensis - Rekha K; Anju M; Sobha S; Sushamakumari S; Thomas K.U (In: Advances and Challenges in Plant Breeding, Biotechnology and Conservation. (Eds. R.B. Smitha; R. Prakashkumar; N.S. Pradeep; K.V. Mohanan and P.V. Madhusoodanan). Malabar Botanical Garden and Institute for Plant Sciences, Kozhikode, India, pp. 219-226.)
The heritable variation within a species is the consequence of the difference in the primary DNA sequence of different individuals. The term epigenetics is generally used to refer the study of heritable change in gene expression that is independent of DNA sequence. Epigenetic changes can result in altered gene transcription and serves as an important mechanism in regulating gene expression during development and in response to stimulus. It is reported that heritable epigenetic marks persists through meiosis and are stably transferred to the next generation resulting in trans-generational epigenetic inheritance. Rubber tree is commercially propagated by bud grafting and the effect of rootstock on the performance of scion is still debated. In the present study we made an attempt to identify the impact of stock scion interaction on the epigenome of rubber by comparing the methylation pattern of uniform, own rooted seedlings and their bud grafted counter parts. Multiple uniform seedlings of Hevea brasiliensis were developed through half ovulo embryo culture method. Genetic as well as epigenetic uniformity of these seedlings was confirmed by RAPD as well as MSAP (Mythylation Sensitive Amplified Length Polymorphism). One among the uniform seedlings was was multiplied by bud grafting to divergent rootstocks and were again tested for their genetic and epigenetic uniformity. The study revealed that there is no genetic variation among the multiple seedlings and among the bud grafted counterparts. However, epigenetic variation was observed among among the bud grafted plants which were maintained under under uniform environmental conditions. Since rootstock is the only source of variation here, it is presumed that the variation was induced by rootstock. The study assumes importance in Hevea because accumulation and maintenance of epigenetic changes during various cycles of vegetative propagation may eventually lead to an altered phenotype and can result in intraclonal variability.
Source Year: 2016
Keywords: Hevea brasiliensis; MSAP; RAPD; Variability